2020
DOI: 10.1103/physrevd.101.024008
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes of black holes and Borel summation

Abstract: We propose a simple and efficient way to compute quasinormal frequencies of spherically symmetric black holes. We revisit an old idea that relates them to bound state energies of anharmonic oscillators by an analytic continuation. This connection enables us to achieve remarkable high-order computations of WKB series by Rayleigh-Schrödinger perturbation theory. The known WKB results are easily reproduced. Our analysis shows that the perturbative WKB series of the quasinormal frequencies turn out to be Borel sum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 42 publications
1
60
0
Order By: Relevance
“…The lowest orders have been found to give very accurate results for high-modes. In [33][34][35] the WKB approximation was studied up to 6th order in (7), where it was found that the frequencies ω must satisfy a specific constraint in terms of V and the coefficients V (k) : (8) where N = n + 1/2 with n = 0, 1, 2, . .…”
Section: Qnm With the Wkb Methodsmentioning
confidence: 99%
“…The lowest orders have been found to give very accurate results for high-modes. In [33][34][35] the WKB approximation was studied up to 6th order in (7), where it was found that the frequencies ω must satisfy a specific constraint in terms of V and the coefficients V (k) : (8) where N = n + 1/2 with n = 0, 1, 2, . .…”
Section: Qnm With the Wkb Methodsmentioning
confidence: 99%
“…We conclude this section with a few observations on the approach proposed in Ref. [25]. First it should be observed that although the Padé transforms,P N N of the series k a k x k /k!…”
Section: The Methodsmentioning
confidence: 85%
“…In this section we shall construct the quasinormal modes of the perturbed Schwarzschild black hole. Although the Padé summation is our method of choice, whenever in doubt, we will also use the Borel-Padé summation [25]. Moreover, all the cases presented in this section have been calculated using the continued fraction method.…”
Section: A the Schwarzschild Black Holementioning
confidence: 99%
“…We utilize the efficient and stable methods [24][25][26][27] that have brought a lot of attention recently. One method we adopt is based on the Borel-Padé summation [24]. The other method we use is the so-called higher order WKB-Padé approach suggested first in ref.…”
Section: Resultsmentioning
confidence: 99%
“…In ref. [24], the results obtained by the Borel-Padé summation and Leaver's method [29] were compared and the consistency of the two methods was determined. Here we can see, e.g from Table 1, that the values obtained by the Borel-Padé summation agrees well with that by the WKB-Padé method when the refractive index is not less than 5 and l is greater than n. For example, we take two sets of data, (η = 5, l = 3, n = 3) and (η = 15, l = 3, n = 0), respectively, and find that the two real parts, 1.179851 and 1.203996 in the first set, differ by 2.01%, and 1.319595 and 1.319663 in the second set, just by 0.07%.…”
Section: Quasinormal Mode Frequencymentioning
confidence: 99%